A comparative study of the volatility and efficiency of commodity futures index roll methods - Rajarshi Aroskar; William A. Ogden (Financial Studies, 2018)
Given the size of the commodity index market, rollovers require large numbers of contracts to be purchased and sold on rollover dates. Index providers are careful in choosing their roll methods in order to minimize volatility and maximize the market efficiency of their indexes. This study investigates the efficiency of various roll methodologies compared to their respective continuous futures series. We compare roll methodologies to see whether they have similar volatility and efficiency characteristics as näive rolling. Daily settlement prices for 15 commodities (precious metals, metals, agriculture, and energy) from each of five index providers (Credit Suisse (CS), Merrill Lynch (ML), Dow Jones - UBS (DJUBS), Diapson (DCI) and Standard and Poor's - Goldman Sachs (GS)) were collected and analyzed. Daily prices for a continuous series of futures contracts (Continuous Futures Series) representing each of the aforementioned commodities is used as a benchmark. Results show that any differences that indexes have with their continuous futures series are dependent on the type of commodity and not on a particular roll methodology. Thus, an investor/ETP investing in commodities should not worry about the roll methodology used by an index provider.
Keywords: G11; G13; G19; 330; futures; contracts; rollover; diversification